Peningkatan Keterampilan Warga Pacul Bojonegoro melalui Pelatihan Pembuatan Media Tanam Hidroponik - Roihatur Rohmah; Lisa Aminatul Mukarromah; HM. Ridlwan Hambali; Mundzar Fahman; Oktavio Bima Saputra (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
The hydroponic method is a method of planting using planting media other than natural soil, including using water. Hydroponic plant cultivation exists in a nutrient solution but not from the soil. The advantage of the hydroponic method is that only uses a narrow land as a medium. By utilizing used glass can also be used to make hydroponic plant cultivation. In this community service activity, training and socialization on hydroponic cultivation were carried out to optimize the narrow land in the community of Pacul Village, Bojonegoro sub-district, Bojonegoro Regency. The activity was carried out by socializing the existence of hydroponic training for residents of Pacul Bojonegoro Village to increasing the public skills. Participants in the training were 31 PKK members. The achievement of the training activities can be seen from the results of the pre-test and post-test. The result of this hydroponic training and socialization is that there is an increase in the information on the assessment of strongly agreeing with the questions and questionnaire statements from 18‒45%.